2017
DOI: 10.17219/acem/62829
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Hepcidin and Nesfatin-I Status in Childhood Iron and Vitamin B12 Deficiency Anemias

Abstract: Background. Anemia is a disease that is long and often repetitive and can result in a great burden to the national economy. The most frequent nutritional deficiency anemias in children are related with iron and vitamin B12 deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Few studies have investigated the effect of indoor air pollution on anemia, although the investigation of chronic effects on blood health is increasing [ 1 , 32 , 33 ]. Current research is limited to assessing the relationship between fuel consumption and anemia in developing countries [ 4 , 32 ], overall outdoor air and anemia [ 8 , 11 ], and the association between anemia in children [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated the effect of indoor air pollution on anemia, although the investigation of chronic effects on blood health is increasing [ 1 , 32 , 33 ]. Current research is limited to assessing the relationship between fuel consumption and anemia in developing countries [ 4 , 32 ], overall outdoor air and anemia [ 8 , 11 ], and the association between anemia in children [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hct refers to the percentage of the volume in contact with red blood cells (RBCs) in whole blood [ 3 ]. The WHO has defined Hb deficiency, the most representative of the BIRA, as <13 or <12 g/dL for men or women, respectively [ 4 ]. MCV is the mean Hb volume, MCH is the average Hb ratio per red blood cell, and MCHC is the Hb ratio per dl.…”
Section: Introductionmentioning
confidence: 99%
“…This response is consistent with the prior demonstration of an association between (1) cell oxidant generation and cytokine production/release and (2) iron availability. Comparable to a decreased availability of metal following particle exposure, iron deficiency in cells, animal models, and humans can be associated with an augmented generation of oxidants. In the same way, different cell types demonstrate a capacity to release of pro-inflammatory cytokines dependent on concentrations of iron. , AMs show the same relationship between levels of levels of cytokine release associated with elevated metal availability following exposures to iron-coated quartz, deferoxamine, endotoxin, and microbials. …”
Section: Discussionmentioning
confidence: 99%
“…During anemia, hepcidin creates an important link between the body’s defense, inflammation, and iron metabolism. A previous study has shown that during infection and inflammation, hepcidin synthesis is considerablely increased owing to stimulation by IL-6 5…”
Section: Introductionmentioning
confidence: 99%